RELIGIOUS TOLERANCE: PERSPECTIVE OF TEACHERS FROM DIFFERENT RELIGIONS IN ELEMENTARY EDUCATION (SD) REMAJA PARAKAN TEMANGGUNG - Muhammad Nur Fadhli; Sangkot Sirait (Sunan Kalijaga International Journal on Islamic Educational Research, 2018)
Abstract: The article is intended to describe the religious tolerance perspective of many teachers from different religions in Primary Education (Sekolah Dasar-SD) Remaja Parakan, Temanggung; to know how the implementation of religious tolerance in the school; and to figure out how the implications of religious tolerance towards the attitude of learners religiosity in the school. By using qualitative methods, data are collected by interviews, observation, and documentation, and analyzed in according do Milles and Hubberman. The article finds that: First, the teacher of Islamic education declares the tolerance is an attitude of mutual respect for various beliefs or religions. Meanwhile, according to the teacher of Christian education, religious tolerance is one's belief in eliminating the ego by respecting other people without looking at their religions. In other words, religious tolerance is an understanding that teaches life to respect the right to freedom of religion. Furthermore, according to the teacher of Buddhist Education, religious tolerance is socializing in the community without carrying religious labels. Second, the internalization of religious tolerance at the school is already quite good, and this is evidenced by the absence of conflict in the name of religion. Third, generally, the religious attitude of students is included in the category of inclusive religious attitudes.